2019
DOI: 10.1021/jacs.9b01283
|View full text |Cite
|
Sign up to set email alerts
|

Suite of Organoplatinum(II) Triangular Metallaprism: Aggregation-Induced Emission and Coordination Sequence Induced Emission Tuning

Abstract: A series of triangular metallaprisms with a kinetically inert Pt−N bond have been synthesized from the stepwise assembly of a Pt-corner, linear linker 4,4′bipy (4,4′-bipy = 4,4′-bipyridine) and triangular ligand [tpb or tpt, tpb = tris(4-pyridyl)benzene, tpt = tris(4pyridyl)triazine]. The use of an unsymmetrical [Pt(HL)]corner (H 2 L = 2,6-diphenylpyridine) leads to novel isostructural products. Phenyl rotation at the metalcorners endows these complexes with good aggregationinduced emission (AIE) function, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Furthermore, when Pt II complexes are close enough (distance below 3.5 ) [11][12][13][14] metallophilic interactions between Pt centers may be established and stable aggregates [15][16][17] can be observed that possess spectroscopic properties which can be dramatically different from those of the monomeric metal complex. [1][2][3][4][18][19][20][21][22][23] In fact, the establishmento fg round state intermolecular interactions between protruding d z 2 orbitals resultsi nt he formation of lower-lying molecular orbitals, thus an ew optical transition appears ascribed to metal-metal-to-ligand charget ransfer (MMLCT). [22][23][24][25][26][27][28] The changes in the optical properties are directly correlated with the distance between the Pt centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Furthermore, when Pt II complexes are close enough (distance below 3.5 ) [11][12][13][14] metallophilic interactions between Pt centers may be established and stable aggregates [15][16][17] can be observed that possess spectroscopic properties which can be dramatically different from those of the monomeric metal complex. [1][2][3][4][18][19][20][21][22][23] In fact, the establishmento fg round state intermolecular interactions between protruding d z 2 orbitals resultsi nt he formation of lower-lying molecular orbitals, thus an ew optical transition appears ascribed to metal-metal-to-ligand charget ransfer (MMLCT). [22][23][24][25][26][27][28] The changes in the optical properties are directly correlated with the distance between the Pt centers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][18][19][20][21][22][23] In fact, the establishmento fg round state intermolecular interactions between protruding d z 2 orbitals resultsi nt he formation of lower-lying molecular orbitals, thus an ew optical transition appears ascribed to metal-metal-to-ligand charget ransfer (MMLCT). [22][23][24][25][26][27][28] The changes in the optical properties are directly correlated with the distance between the Pt centers. [6,11,[29][30][31] Thus, the shorter the distance is, the stronger the electronic Pt•••Pt electronic interaction is, and the more bathochromically shiftedt he MMLCT band is.…”
Section: Introductionmentioning
confidence: 99%
“…The emission intensity of 4 surprisingly decreased when the hexane content is still increasing. A large number of metallaprism molecules aggregated together and formed large nano‐particle, thus inducing the transformation from suspension liquid to visible solid and the concentration of 4 significantly decreased [27–28] . The Φ F values of 4 were 0.5 % and 0.7 % in CH 2 Cl 2 and CH 2 Cl 2 /hexane mixture (60 % hexane), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Huang and Hor reported that a series of triangular metallaprisms with kinetically inert PtN bonds were synthesized from the stepwise assembly of a Pt‐corner, linear linker 4,4′‐bipyridine and triangular ligand (tpb or tpt, tpb = tris(4‐pyridyl)benzene, tpt = tris(4‐pyridyl)triazine) ( Figure A). [ 82 ] Utilization of an unsymmetrical [Pt(HL)]‐corner (H 2 L = 2,6‐diphenylpyridine) led to novel isostructural products and the phenyl rotation at the metal corners, endowed these complexes with good AIE features. The self‐assembly process of building blocks and AIEgens into metallacages was also reported as shape‐controllable.…”
Section: Construction Of Aiegens‐based 3d Frameworkmentioning
confidence: 99%
“…Reproduced with permission. [ 82 ] Copyright 2019, American Chemical Society. B) Schematic illustration of the heteroligation‐directed self‐assembly of 90° Pt(II) acceptors and pyridyl and carboxylate ligands.…”
Section: Construction Of Aiegens‐based 3d Frameworkmentioning
confidence: 99%